2023
DOI: 10.1029/2023sw003476
|View full text |Cite
|
Sign up to set email alerts
|

The Ionospheric Effects of the 2022 Hunga Tonga Volcano Eruption and the Associated Impacts on GPS Precise Point Positioning Across the Australian Region

Abstract: The Hunga Tonga Volcano eruption launched a myriad of atmospheric waves that have been observed to travel around the world several times. These waves generated traveling ionospheric disturbances (TIDs) in the ionosphere, which are known to adversely impact radio applications such as Global Navigation Satellite Systems (GNSS). One such GNSS application is Precise Point Positioning (PPP), which can achieve cm‐level accuracy using a single receiver, following a typical convergence time of 30 min to 1 hr. A networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…8b), and in Japan at about 11 UT (Fig. 8c), which corresponds to the arrival of TIDs in those regions (e.g., Carter et al 2023;Saito 2022;Lin et al 2022;Shinbori et al 2022). The vertical velocity of the gravity waves decreases rapidly as they move away from HTHH, and becomes insignificant at about 14 UT (Fig.…”
Section: Propagation Of Atmospheric Wavesmentioning
confidence: 85%
“…8b), and in Japan at about 11 UT (Fig. 8c), which corresponds to the arrival of TIDs in those regions (e.g., Carter et al 2023;Saito 2022;Lin et al 2022;Shinbori et al 2022). The vertical velocity of the gravity waves decreases rapidly as they move away from HTHH, and becomes insignificant at about 14 UT (Fig.…”
Section: Propagation Of Atmospheric Wavesmentioning
confidence: 85%
“…The CVID and TIDs can change the propagation environment of radio waves to some extent, thus affecting the performance of GNSS navigation and positioning [31][32][33]. In addition, Carter et al [34] found that small-scale ionospheric disturbances triggered by volcanic eruptions in Tonga increased the convergence time of the precise point position.…”
Section: Introductionmentioning
confidence: 99%